Mladi govorci slovenskega jezika v Italiji in njihov odnos do Republike Slovenije - Brezigar, Sara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
On the 30th anniversary of independence of the Republic of Slovenia, the article offers an insight into the basic social and cultural characteristics of the population of young speakers of Slovene in Italy. The authors attempt to define the role that young Slovene speakers in Friuli - Venezia Giulia can play in the common Slovene space and explore their attitudes towards the Republic of Slovenia on an emotional, symbolic and practical level. In doing so, they rely mainly on research conducted over the last fifteen years. They conclude that this population is not fully centred on preserving traditional cultural values and language: it is primarily a population with high human and intellectual potential, which is already an important player in cross-border and other forms of cooperation along the Slovene-Italian border and attaches greater value to multilingualism than to nationality, ethnicity and the development of the Slovene minority in Italy.
Keywords: attitudes towards the Republic of Slovenia; identiteta; identity; Italija; Italy; mladi; odnos do Republike Slovenije; raba jezika; Slovenci v Italiji; Slovene speakers; Slovenes in Italy; slovenščina; youth